Clinical Anatomy and Possible Clinical Significance of the Postcentral Branches of Spinal Arteries in the L1–L5 Levels. Issue 8 (October 2020) - Zhao, Qinghao; Zhong, Enyi; Shi, Benchao; Ding, Zihai; Jin, Dadi; Li, Qingchu
Abstract : Study Design: This was a dissection-based study of 10 embalmed human cadavers. Objective: The objective of this study was to identify and describe the postcentral branches in the L1–L5 intervertebral foramina (IVF) and to determine their possible clinical significance. Summary of Background Data: The lower lumbar segmental arteries have been well studied. However, there are few articles with regard to the postcentral branches in the L1–L5 IVF. Materials and Methods: Eighty L1–L5 IVF from 10 embalmed cadavers were studied with a surgical microscope, and the postcentral branches were identified. The branches, origin, insertion, and spatial orientation of the postcentral branches in the L1–L5 IVF were examined. The diameter of the arteries was measured using a Vernier caliper. Results: In our study, the occurrence rate of a postcentral branch was 100.00% in the 80 IVFs. The postcentral branch was routinely divided into the following 2 types: type 1, postcentral branch main trunks (65.00%), which branch from the spinal arteries or lumbar arteries and then divide into 2 branches (superior and inferior branches), and type 2, superior and inferior branches, which branch straight from the spinal arteries (35.00%). The initial portion of the postcentral branches traveled around the anterolateral edge of the disk to the dorsum. Conclusions: Postcentral branches of spinal arteries are common structures in IVF; there are 2 types of postcentral branches. Thorough understanding of the spinal arteries before percutaneous endoscopic lumbar discectomy may be an important step in reducing intraoperative bleeding and ensuring clear visualization, which may result in significant benefits for patients.